Innovative Music Composition “Blabur” | Karya Musik Inovatif “Blabur” - Ardi Gunawan Ardi; Santosa Hendra (GHURNITA: Jurnal Seni Karawitan, 2023)
Blabur is defined as a source of imagination and pouring out ideas that will later be able to reflect both natural disaster phenomena and offer ideas through works of art. Blabur's innovative music works use spoken media which focuses on Gender Wayang on the instruments of drum krumpungan, gong pulu, kecek ricik, flute, gantora and kajar with the aim of knowing the ideas, structure and concept of making Blabur's innovative music works. Through the creation of this work, stylists want to develop existing patterns from before. Blabur's innovative musical work was appointed as a work as a reflection and a message to us that if the natural forces are so great if they experience an imbalance, they will become a disaster. The process of creating Blabur's innovative musical works has gone through three stages, namely the Exploration stage, the Improvisation stage, and the Forming stage. Blabur's innovative musical work consists of three main parts, namely part one, part two and part three. This work is supported by ten musicians and one gerong from Sanggar Mekar Seruni with a duration of 13 minutes and 14 seconds.